The development of a telemetry and position indicating system for a diver - Samo, Khalid (Fakulti Sains dan Teknologi, 2010)
In a diving expedition safety is important both to the personnel on board the support boat and the divers. A diver needs to know their bearing and range to the support boat as diving progress to navigate freely in the water and to return to the boat immediately in time of emergency or after completing a task. Ideally, this may be achieved by computing the diver's bearing and range periodically using an underwater tracking system fitted on a support boat and transmitting the information back to them by acoustic means. However, despite the availability of electronic based diver tracking systems, no attempt was made to exploit this idea. The reason being the extensive and rapidly time-variant multipath echoes generated in a shallow water made it difficult to process the coded information if transmitted at high rates due to signal masking. Also, air bubble noise generated through breathing, physical movement and biological noise from snapping shrimps hinders effective propagation and reception of the data signals in the water.